Analisis Pengaruh Tanaman Melati Air sebagai Fitoremediasi dalam Mengatasi Pencemaran Air Limpasan Stockpile Batubara - Andre Cahyo Ramadhani; Rico Januar Sitorus; Muslimin Muslimin; Ririn Noviyanti Putri; Rima Ernia (Universitas Batanghari Jambi, 2023)
Acid mine drainage can be generated by coal stockpile piles, especially if the sulfur content is high which can have an impact on environmental health. The impact of coal stockpile runoff water pollution can be overcome by treating wastewater using phytoremediation. The author conducted a phytoremediation experiment using Echinodorus palaefolius plants with samples of coal stockpile runoff taken from the inlet of KPL C PT Bukit Asam Tbk Unit Dermaga Kertapati in June - August 2022, the experiment was carried out using three different treatments, namely 600gr, 700gr and 900gr which were observed for 7 days with parameters of pH, TSS, temperature and plant morphology. The results of the study showed that the pH parameter in the sample of 600 grams of plants, neutral pH was reached on the 4th day with a value of 6.03, in the sample of plants, 700 grams of neutral pH was reached on the 3rd day with a value of 6.11, on the treatment of plant samples. 900 gr neutral pH was reached on day 2 with a value of 6.10. On the TSS parameter, in all plant sample treatments, on day 2 the TSS value has reached the environmental quality standard value of 200 mg/l and the TSS value is decreasing day by day with the highest removal efficiency value obtained at 89.0% of the sample treatment. 900 gr plants on the 7th day. In the temperature parameter, the temperature value in the sample is relatively constant with temperatures ranging from 27.4Â°C - 31Â°C, which means it is still in normal conditions according to the required environmental quality standards. In the morphology of the Echinodorus palaefolius plant for 7 days, the plant underwent physical changes with some leaves withering and drying but there were also new shoots that appeared on the plant, but in general the water jasmine plant was able to survive and grow in the coal stockpile runoff water samples.